166k views
2 votes
Wat is (12+6-5*3)*(2*2+1-7+2)=

2 Answers

2 votes

Answer:


\Huge \boxed{{0}}

Explanation:


(12+6-5*3)*(2*2+1-7+2)

Solve brackets.


(12+6-15)*(4+1-7+2)


(3)*(0)

Multiply both numbers.


3 * 0 = 0

User Roark
by
4.5k points
4 votes

Answer:


\huge\boxed{0}

Explanation:

First we have to do the operation of multiplication

=> (12+6-15)*(4+1-7+2)

Now, Solving the terms inside the brackets

=> (18-15)*(5-7+2)

=> (3)*(-2+2)

=> (3)*(0)

=> 0

User Paolo Rovelli
by
4.9k points